Pengujian Kualitas Situs Web Pemerintahan Kabupaten Malinau Menggunakan Metode McCall - Alexander David Christian Subroto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The Malinau Regency, in utilizing the internet, created a website that aims to provide news or information for the Malinau community, so that it is easier for the Malinau community to obtain and find out information in the Malinau Regency environment. But the recently updated Malinau Regency website has never been tested for website quality. Knowing the quality of the website is very important for developers, because by knowing the quality of the website making the goals in web development be clearer. By using the questionnaire and observation data collection method, the results of these data were obtained, then the data were analyzed using the McCall method and the result was that the Malinau Regency website was very good, although the Efficiency Quality Factor scored 57.5% or quite good.